(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The study group included 26 children with simple febrile seizures, the second group - 24 children with afebrile seizures that developed after an episode of fibril seizures. All children underwent targeted clinical, neurological, laboratory and instrumental examinations.